2016
DOI: 10.1186/s12943-016-0497-3
|View full text |Cite
|
Sign up to set email alerts
|

Does VEGF facilitate local tumor growth and spread into the abdominal cavity by suppressing endothelial cell adhesion, thus increasing vascular peritoneal permeability followed by ascites production in ovarian cancer?

Abstract: BackgroundOvarian cancer is mostly associated with pathologically regulated permeability of peritoneal vessels, leading to ascites. Here, we investigated the molecular regulation of endothelial permeability by the vascular endothelial growth factor (VEGF) and both tight and adherens junction proteins (VE-cadherin and claudin 5) with regards to the tumor biology of different ovarian cancer types.MethodsSerum and ascites samples before and after surgery, as well as peritoneal biopsies of 68 ovarian cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 28 publications
3
30
0
2
Order By: Relevance
“…In the current study, we found Nectin‐2 localized in the peritoneal vasculature. This is in line with the results of our previous studies where colocalization of the adhesion proteins claudin 5 and VE‐cadherin, as well as decreased expression in the peritoneum of ovarian cancer patients, was found . In the current experiment, Nectin‐2 was clearly suppressed in the peritoneal endothelium of tumor patients as compared to controls, associated with highly expressed VEGF in the tumor and increased VEGF serum levels indicating that Nectin‐2 downregulation might be VEGF driven.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the current study, we found Nectin‐2 localized in the peritoneal vasculature. This is in line with the results of our previous studies where colocalization of the adhesion proteins claudin 5 and VE‐cadherin, as well as decreased expression in the peritoneum of ovarian cancer patients, was found . In the current experiment, Nectin‐2 was clearly suppressed in the peritoneal endothelium of tumor patients as compared to controls, associated with highly expressed VEGF in the tumor and increased VEGF serum levels indicating that Nectin‐2 downregulation might be VEGF driven.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous investigations, we showed that increased peritoneal vascular permeability is due to VEGF‐induced suppression of adhesion molecules in the peritoneal vasculature . Furthermore, we showed that VEGF‐derived ascites formation increases with aggressive ovarian cancer subtypes . In the current study, we found Nectin‐2 localized in the peritoneal vasculature.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Elevated VEGF levels are related to greater vascular permeability and increased tendency towards peritoneal progression and ascites [70]. A meta-analysis including over 1000 ovarian cancer patients confirmed that elevated serum VEGF levels were associated with shorter progression-free survival (HR 2.46; 95% CI 1.84-3.29) and lower overall survival (HR 2.21; 95% CI 1.57-3.13) compared with low levels.…”
Section: Angiogenesis-related Biomarkersmentioning
confidence: 96%